The effect of freeze-dried Lactiplantibacillus plantarum I on the microbiological quality of queen scallop Aequipecten opercularis - Kostelac Deni; Markov Ksenija; Čanak Iva; Kovačić Ines; Žunec Ante; Frece Jadranka (Croatian Journal of Fisheries)
In this study, four selected strains of lactic acid bacteria of marine origin were freeze-dried using skim milk as a cryoprotectant. After freeze-drying, survival rates were determined under 24-hour exposure to seawater samples. Isolate Lactiplantibacillus plantarum I had the highest survival rate of 92.5% and was selected for further experiments. Freeze-dried Lpb. plantarum I strain was added to queen scallop Aequipecten opercularis (Linnaeus 1758) in circular basins under climate change conditions (temperature and pH modifications) for one month. After the feeding period, shellfish were collected and microbiological quality was determined for each scallop. The results indicate that the addition of Lpb. plantarum I significantly improved the microbiological quality of the cultivated scallops. The total number of bacteria together with Staphylococcus species was significantly reduced, and the added lactic acid bacteria strain was maintained at desired amounts during the entire feeding period. The results obtained indicate that the inclusion of Lpb. plantarum I as a dietary supplement could provide protection against pathogens and serve as a feasible approach to reduce infection levels when cultivating A. opercularis in captivity.